Fiscal sustainability in the presence of systemic banks: The case of EU countries - Agnès Bénassy-Quéré; Guillaume Roussellet (Center for Economic Studies and ifo Institute (CESifo), 2012)
We provide a first attempt to include off-balance sheet, implicit insurance to SIFIs into a consistent assessment of fiscal sustainability, for 27 countries of the European Union. We first calculate tax gaps à la Blanchard (1990) and Blanchard et al. (1990). We then introduce two alternative measures of implicit off-balance sheet liabilities related to the risk of a systemic bank crisis. The first one relies of microeconomic data at the bank level. The second one relies on econometric estimations of the probability and the cost of a systemic banking crisis, based on historical data. The former approach provides an upper evaluation of the fiscal cost of systemic banking crises, whereas the latter one provides a lower one. Hence we believe that the combined use of these two methodologies helps to gauge the range of fiscal risk.
Keywords: H12; H63; H81; 330; fiscal sustainability; tax gap; systemic banking risk; off-balance sheet liabilities; Öffentlicher Haushalt; Nachhaltigkeit; Bankenkrise; Systemrisiko; Steueraufkommen; EU-Staaten